Experimental Study on Mechanical Properties of Polypropylene: Steel Fiber Concrete and Loading Characteristics of Shaft Lining. (25th April 2022) - Qin, Bendong; Li, Shuo; Guo, Jiaqi; Liu, Shaofeng; Liu, Xiliang; Lai, Yongbiao; Li, Hailiang
Abstract : With the rapid consumption of shallow coal resources, the depth of shaft lining construction continues to increase; huge formation pressure and complex geological conditions make the stress condition of shaft lining become more complex. The concrete strength grade is usually enhanced to improve the bearing capacity of shaft lining; however, high strength grades bring high brittleness. In order to solve the problem of high brittleness of high-strength concrete shaft lining in ultra-deep mine construction, a steel-polypropylene hybrid fiber high-performance reinforced concrete (SPHFRC) shaft model was developed. The SPHFRC with various mix proportions was prepared by optimizing the fiber content. The mechanical properties of SPHFRC were tested and compared with the reference concrete (PHSC). The results show that the SPHFRC can be obtained by adding the volume fraction in 1.2% steel fiber and 1.0% polypropylene fiber, which increases the tensile strength by 27.5% and the compressive strength of SPHFRC was similar to the reference concrete. By introducing a new brittleness evaluation index B to evaluate the brittleness of concrete, the results show the fiber greatly improves the brittleness problem of PHSC. Afterwards, a model test of PHSC and SPHFRC shaft lining was conducted, and the circumferential and axial load-stress-strain curves and load-displacement curves of concrete and steel bars are analyzed. Combining the failure characteristics of the two shaft lining models, the following conclusions are obtained: The ultimate bearing capacity of PHSC shaft lining is hardly affected by fibers, but the hoop displacement is significantly reduced and the circumferential stability of shaft lining has been greatly improved, the initial cracks appeared late, the speed of crack's propagation is reduced, and no obvious concrete peeling and separation appeared during damage. The comprehensive performance of SPHFRC shaft lining is excellent, which has better ductility and anti-deformation ability.